Board diversity and firm performance in the construction, manufacturing, and trading/services industries - Syajarul Imna Mohd Amin,; Shifa Mohd Nor, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research investigates the effect of board diversity on Malaysia’s firm performance from an industry specificities angle. The study focuses on three major industries i.e. construction, manufacturing, and trading/services (CMTS) from the year 2012 to 2016. Board personalities measure gender and ethnicity while board characteristics indicate managerial ownership, board size, board independence, and CEO duality. The results obtained proposed that board independence, CEO duality, gender diversity, and managerial ownership are significant factors affecting firm performance. Meanwhile, board size and ethnic diversity are not significant. The results are different due to the differences in industry specialisations. In sum, the mixed evidence implies that Malaysian industries’ sectors are not homogenous and unique by nature.